Different presentations of mevalonate kinase deficiency: a case series. - De Pieri, Carlo; Taddio, Andrea; Insalaco, Antonella; Barbi, Egidio; Lepore, Loredana; Ventura, Alessandro; Tommasini, Alberto (Clin Exp Rheumatol, 2015)
OBJECTIVES: We aimed to raise awareness among paediatricians and physicians about this often misunderstood condition. METHODS: We discussed the clinical profiles associated with late or wrong diagnosis of mevalonate kinase deficency (MKD) in a single centre case series. RESULTS: We analysed the most common challenges and pitfalls that a clinician might face during the diagnostic process. Five main clinical profiles were characterised. CONCLUSIONS: We propose a new perspective on MKD, suggesting that the presentation of this disease can vary from patient to patient.
Keywords: Age Factors; Bacterial Infections; Child; Child, Preschool; Diagnosis, Differential; Diagnostic Errors; Female; Genetic Predisposition to Disease; Humans; Infant; Inflammatory Bowel Diseases; Male; Mevalonate Kinase Deficiency; Phenotype; Predictive Value of Tests; Recurrence; Risk Factors; Sepsis; Vasculitis; Young Adult